HUBUNGAN MOTIVASI DAN MASA KERJA DENGAN PRODUKTIVITAS PEKERJA DI HOME INDUSTRY - Dinda Laminia; Lailatul Muniroh (The Indonesian Journal of Occupational Safety and Health, 2018)
Motivation of work needed for worker to be productive. In addition, the work period that has been taken can be one determinant factor of work productivity and the productivity of work comparing by the result of work with the time required when doing the job. The purpose of this research was to determine and learn the relationship between work motivation and work period with productivity at Home Industry X. This research is an analytic observational research with cross sectional approach. The variables of this research were work motivation, work period and work productivity. Sample size of this research was 41 respondents taken by simple random sampling and the population were 45 respondents. Data collected by interviewing work period and work motivation interview. The data was analysed by Pearson and Chi – Square test. The result showed that there was correlation between work motivation with productivity (p = 0.000), and there was no relationship between work period with productivity (p = 0.829). The conclusion of this research is there is correlation between work motivation with productivity, where the most of respondents have excellent work motivation and can reach the production target. The higher the motivation was followed by the higher of productivity, whereas the work period of the respondent’s work is not related to productivity.Keywords: home industry, work motivation, work period, work productivity